The Color Change of Natural Blue Sapphires by Heat Treatment - Treedej Kittiauchawal; Pichet Limsuwan (Agriculture and Natural Resources, 2007)
This research aimed to investigate the effects of heat treatment on color and clarity of blue sapphires. The blue sapphires were heated at sequentilly increasing temperature of 1300, 1400, 1500 and 1600 °C in nitrogen atmosphere. Each temperature, the samples were treated for 12 hours, before and after heat treatment at each temperatures, the color and clarity were measured by spectrophotometer. It was found that, when blue sapphires were heated at high temperatures, the color of the untreated sapphire crystal changed to darker blue at higher temperatures. Whereas, the clarity of all samples were not significantly found in the temperature range of 1300 -1600°C .